2010
DOI: 10.1007/s00421-010-1361-6
|View full text |Cite
|
Sign up to set email alerts
|

Are calcineurin genes associated with endurance phenotype traits?

Abstract: Polymorphisms in calcineurin genes are candidates to explain individual variations in endurance phenotype traits owing to the pivotal role that the calcineurin signaling pathway plays in the regulation of important cardiac and skeletal muscle phenotypes such as slow myosin heavy chain expression, skeletal muscle oxidative capacity or cardiac hypertrophy. We studied the possible association of 55 polymorphisms in the calcineurin gene isoforms PPP3CA, PPP3CB, PPP3CC, PPP3R1 and PPP3R2 with both baseline levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
(57 reference statements)
0
12
1
Order By: Relevance
“…He et al [65,66] conducted two association studies of 55 polymorphisms in five genes encoding the calcineurin protein subunits in a group of 102 healthy young Chinese men of Han origin with VO 2max , running economy and echocardiographic variables measured before and after 18-week endurance training program. Results showed significant association between the PPP3CB gene rs3763679 C/T polymorphism with resting heart rate and PPP3CA gene rs2850965 G/T and rs3804423 A/G polymorphisms with baseline VO 2max .…”
Section: Calcineurin/nfat-related Genetic Markers (Nfatc4mentioning
confidence: 99%
“…He et al [65,66] conducted two association studies of 55 polymorphisms in five genes encoding the calcineurin protein subunits in a group of 102 healthy young Chinese men of Han origin with VO 2max , running economy and echocardiographic variables measured before and after 18-week endurance training program. Results showed significant association between the PPP3CB gene rs3763679 C/T polymorphism with resting heart rate and PPP3CA gene rs2850965 G/T and rs3804423 A/G polymorphisms with baseline VO 2max .…”
Section: Calcineurin/nfat-related Genetic Markers (Nfatc4mentioning
confidence: 99%
“…For our study, we selected the tag SNPs using haploview that have a reported minor allele frequency C0.1. This includes a total of 55 SNPs, 34 located in PPP3CA, 3 in PPP3CB, 12 in PPP3CC and 3 in each of PPP3R1 and PPP3R2 (Supplementary File 1) (He et al 2010). …”
Section: Selection Of Tag Single Nucleotide Polymorphismsmentioning
confidence: 99%
“…Insertion/deletion polymorphisms within the PPP3R1 promoter region have been associated with left ventricular hypertrophy and the sensitivity to training for muscular strength (10,11). Previous reports have also indicated that some variants produce CN with different activity levels and are correlated with better exercise endurance in elite athletes (12,13). However, few studies have investigated the correlation between polymorphisms within the genes encoding CN and response to aerobic training in a general population.…”
Section: Introductionmentioning
confidence: 99%
“…All participants underwent 5000-meter steady aerobic running outside on a track, 3 times per week, for a total of 18 weeks, as in a prior report (13). Before 5000-meter aerobic running, 2-week adaptive training was performed with 1000-meter and 3000-meter running at the first and second week.…”
Section: Methodsmentioning
confidence: 99%